Performance of the Pooled Cohort atherosclerotic cardiovascular disease risk score in hepatitis C virus‐infected persons. Issue 10 (10th April 2017) - Chew, K. W.; Bhattacharya, D.; Horwich, T. B.; Yan, P.; McGinnis, K. A.; Tseng, C.; Freiberg, M. S.; Currier, J. S.; Butt, A. A.
Summary: Chronic hepatitis C virus (HCV) infection has been associated with an increased risk for cardiovascular disease (CVD). The recommended Pooled Cohort atherosclerotic cardiovascular disease (ASCVD) risk equation for estimation of 10‐year CVD risk has not been validated in HCV‐infected populations. We examined the performance of the ASCVD risk score in HCV‐infected persons, using the national Electronically Retrieved Cohort of HCV Infected Veterans to derive a cohort of HCV‐infected and uninfected subjects without baseline ASCVD, hepatitis B, or HIV infection, and with low‐density lipoprotein cholesterol level<190 mg/dL. Performance of the ASCVD risk equation was assessed by Cox proportional hazard regression, C‐statistics and Hosmer‐Lemeshow statistic. The cohort included 70 490 HCV‐infected and 97 766 HCV‐uninfected men with mean age of 55 years, 56% White and 29% Black. Incident CVD event rates were similar between the two groups (13.2 and 13.4 events/1000 person‐years), with a higher incidence of coronary heart disease events in the HCV‐uninfected group and of stroke events in the HCV‐infected group. Adjusting for ASCVD risk score, HCV infection was associated with higher risk for an ASCVD event in the subgroup with baseline ASCVD risk ≥7.5% (HR: 1.19, P <.0001). C‐statistics were poor in both the HCV‐infected and uninfected groups (0.60 and 0.61, respectively). By Hosmer‐Lemeshow test, the ASCVD risk equation overestimated risk amongst lower risk patients and underestimated risk amongst higher risk patients in both the HCV‐infected and uninfected groups. Further investigation is needed to determine whether a modified equation to accurately predict ASCVD risk in HCV‐infected persons is warranted.